AN ANALYSIS OF STUDENTS’ CHEATING BEHAVIOR IN DOING ENGLISH ASSESSMENT AT THE 8TH GRADE OF SMP N 1 TIGO NAGARI - Husnul Fatimah; Eliza; Widya Safitri; Irwandi Natsir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Cheating has become a widespread problem in educational settings and is frequently reported as a challenge in the classroom. Students often engage in dishonest practices during assignments, daily tests, and examinations, such as copying, whispering, and asking peers for answers. This behavior not only undermines the fairness of assessment but also hinders the development of honesty and responsibility in learning. The research aims to find the internal and external factors do contibute to students’ cheating behavior in doing English assessment. The research employed a descriptive quantitative approach, utilized a questionnaire as the instrument. The population were seventh grade students, the total of the population was 185 students. To determine the sample researcher used simple random sampling. Data were collected through a questionnaire and analyzed using percentage formula. The researcher distributed a questionnaire to each sample randomly. The total of the sample were 46 of students. The result of this research on students’ cheating behavior in doing English assessments found that 46,3% of students engaging in cheating. The findings revealed that both personal and external factors contributed to students’ cheating behavior. Internal factors included poor decision making, low self-efficacy, self-confidence and, lazy attitud. External factors included peer effect, weak moral education, and teacher factors. The study concludes that students’ cheating behavior in English assessments is influenced by both personal and external factors.